2017
DOI: 10.18203/2319-2003.ijbcp20170821
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Picrorhiza kurroa on Alzheimer’s disease induced by aluminium chloride in rats

Abstract: Background: Alzheimer’s disease is a progressive neurodegenerative disorder characterized by cognitive deterioration together with declining activities of daily living and behavioural changes. The present work is aimed to investigate the effect of methanolic extract of rhizomes of Picrorhiza kurroa against aluminum chloride induced Alzheimer’s disease.Methods: Wistar rats were selected in this study and were divided into 5 groups (6 each). Group I served as normal control. Group II received aluminum chloride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this study, Aluminum (B) affected the integrity of the Nissl bodies granulation in the neuron milieu (Yokel 2005) as the progression of free radicals generation seen in group B (Fig. 4B), led to disruption of cell integrity demonstrated by vacuolation within the neuropil and chromatolysis affecting the integrity of the neurons a pathophysiology of AD (Chino et al 2005;Reddy et al 2017) associated with oxidative stress (Asher and Guilford 2016) and loss of neuron histological integrity (Giancarlo et al 2018, Praveenkumar et al 2019. NAC protects pyramidal neurons from chromatolysis of Nissl bodies as seen in the increased granulation of Nissl a representation of ribosome synthesis within the neuron cytoplasm require for neuron repair and neurotransmitter synthesis (Akinrinade et al 2015a(Akinrinade et al , 2015bCiroma et al 2018;Giancarlo et al 2018 hence improving neuron appearance seen in Groups C and D as compared to Group B (Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this study, Aluminum (B) affected the integrity of the Nissl bodies granulation in the neuron milieu (Yokel 2005) as the progression of free radicals generation seen in group B (Fig. 4B), led to disruption of cell integrity demonstrated by vacuolation within the neuropil and chromatolysis affecting the integrity of the neurons a pathophysiology of AD (Chino et al 2005;Reddy et al 2017) associated with oxidative stress (Asher and Guilford 2016) and loss of neuron histological integrity (Giancarlo et al 2018, Praveenkumar et al 2019. NAC protects pyramidal neurons from chromatolysis of Nissl bodies as seen in the increased granulation of Nissl a representation of ribosome synthesis within the neuron cytoplasm require for neuron repair and neurotransmitter synthesis (Akinrinade et al 2015a(Akinrinade et al , 2015bCiroma et al 2018;Giancarlo et al 2018 hence improving neuron appearance seen in Groups C and D as compared to Group B (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…There is need for new drug discovery to combat this menace as it is reported that 75% of the thirty-six million people worldwide affected with dementia are estimated to be AD patient, and it is predicated that 1 in 85 people will be affected by 2050 (Bhattacharya et al 2014). AD is commonly seen in elderly (>65 years) but occurs in young individuals because of lifestyle, stress, depression, frustration and occupation (Reddy et al 2017). There are drugs that clinically prove symptomatic relief for AD such as donepezil, rivastigmine, memantine, tacrine, and galanthamine (Bachurin et al 2017).…”
Section: Introductionmentioning
confidence: 99%